School Wide Early Literacy Screening : A Comparison of PALS-K and AIMSweb Tests of Early Literacy - Butterfuss, Reese M.; Meyer, Danielle (My University, 2015)
The purpose of this study was to examine the differences between PALS-K and AIMSweb assessments.
Color poster with text and tables.
Keywords: AIMSweb; Literacy; STAR early literacy; Phonological Awareness Literacy Screening-Kindergarten (PALS-K); Posters